Association between dietary related factors and central obesity among married women: China Health and Nutrition Survey. (1st January 2022) - Cui, Lingling; Chen, Tingting; Li, Zhonglei; Yu, Zengli; Liu, Xinxin; Li, Jiaxin; Guo, Yingying; Xu, Dongmei; Wang, Xian
Abstract: Waist-to-height ratio (WHtR) with a cut-off value of 0.5 has been recognized as an anthropometric indicator of central obesity to predict the risk of the chronic disease. The aim of our study was to identify dietary related risk factors of central obesity based on WHtR. We used cross-sectional data from the China Health and Nutrition Survey (CHNS) in 2011 obtained from 2881 married women aged 19–55. The association of dietary related factors and central obesity was analyzed using binary logistic regression and back-propagation artificial neural network. Overall, central obesity prevalence was 48.4% (1394/2881). Compared to the population of women without central obesity, the population of women with central obesity had an older average age (41.84 ± 6.89 years vs 38.45 ± 7.91 years, P  < 0.001), and meanwhile an average lower per capita annual income (13904 ± 15916 CNY vs 16753 ± 19163 CNY, P  < 0.001). Our analysis indicated that the score of dietary knowledge (adjusted odds ratio (a OR ), 0.956; 95% confidence interval ( CI ), 0.936–0.976) and the score of food preferences (a OR, 0.961; 95% CI, 0.926–0.997) were significantly associated with lower risk of central obesity; whereas fast food (a OR, 1.002; 95% CI, 1.000–1.003) was associated with higher risk of central obesity. The study showed the score of dietary knowledge (15.5%), fast foods (10.2%), and the score of food preferences (8.8%) were the most important modifiable factors for central obesity. In summary, aging, fast food intake, and lower per capita annual income were positively associated with higher prevalence of central obesity, while higher scores of dietary knowledge and food preferences were negatively correlated. More nutrition education programs should be implemented by the government to strengthen the pro-healthy dietary behaviors. Highlights: Higher scores of dietary knowledge and food preferences were associated with lower risk of central obesity. Age was the most important unmodifiable independent risk factor for predicting central obesity. Dietary knowledge was the most important modifiable independent risk factor for predicting central obesity.